Estrés psicosocial oxidativo ecológico (estrés psoe), caos social y teoría de la complejidad médico social - Jauregui Sagástegui, José Severo (2009)
In the beginning was the Big Bang, Genesis, The Beginning, the main stress of being - not being, and emerged the first protein molecule to the gene and with the passing of time was emerging principles that govern life, the first for distinguished from the inhospitable environment of Autonomy, then to preserve the constancy of the internal environment the principle of homeostasis, then the whole effort of evolution to the emergence of consciousness in humans and its principle of humanity. These are the three principles that govern biological Physiology and enabling you to apply to society to discuss social Physiology, and corresponds with the binomial emponderante education, health, financial and enterprise security, respectively, which are respectively pathophysiological distorting Corruption, Drug Trafficking and Poverty. With the human being emerged from the thinking and personal development in mythical-religious, philosophical and scientific. Collective thinking no deviation in the two great currents visible with its origin in eastern India and western Greece, and a current term as invisible perennis philosophy called synthesis. The three schools with the passage of time formed to lead the three major global institutions of mankind: The Science, The Democratic Capitalist State and Religion, which correlates with the three fundamental principles of life, autonomy, homeostasis and Humanity. Scientific Thinking, developed and consolidated into three major scientific paradigms: the paradigm of scientific logic and simplicity, the cognitive paradigm and philosophy of mind, and the paradigm of complex systems. In the cognitive development of science was evident the need for ontological epistemological foundations for understanding the complex phenomena of ecological oxidative psychosocial stress (Stress PSOE) and Macro Stress individual or social chaos or Macro Stress, wear governing organizations and the human corporeality and the institutions of society. The epistemological ontological principles are: concience (Awareness), Interior; Spirituality; autonomic (Autonomy); Homeonimicidad (Homeostasis); heteronomous (Humanity), Mind, Energy (energy) relational complexity Dialogue (dilemma-paradoxical) Buclicidad ( Cyclicity); recursion or recursive causality, begin (emergence). The mode of interaction between the principles is loop tetralógico with its elements of chaos, order, organization, network and relationships or emergency meetings or undertaken resulting in an evolutionary process of continuous improvement of the quality of being.